Antioxidants in the Treatment of Chronic Diffuse Liver Diseases (the Results of the “MAXAR” Observational Program) - M. V. Mayevskaya; V. T. Ivashkin; V. D. Lunkov; S. P. Kryzhanovskiy; I. Yu. Pirogova; Ch. S. Pavlov; M. S. Zharkova; A. G. Beniashvili; M. A. Morozova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
In the Russian Federation, liver diseases are most frequently represented by two their nosological forms, i.e., nonalcoholic and alcoholic fatty liver disease (NAFLD and ALD). A successful management of such patients, along with improving the functional state of the liver, requires a careful analysis of patients’ nonspecific complaints. In particular, it is important to investigate asthenic syndrome, which can indirectly result in the exacerbation of liver diseases, thus incurring additional economic costs to national healthcare systems. Therefore, the elucidation of the nature of asthenic syndrome and a search for methods for its resolution seem to be highly relevant research tasks.Aim. This study aims to investigate the effect of the antioxidant drug (the extract of the Amur maackia wood) on the organic and functional components of asthenic syndrome in patients with NAFLD and ALD, who do not show signs of the disease decompensation. Materials and methods. An observational program was carried out under the conditions of daily clinical practice in three Russian cities: Moscow, Chelyabinsk and Vladivostok. 80 patients (40 with NAFLD, 40 with ALD) were comprehensively examined according to a developed program. A number of laboratory indicators that reveal inflammatory processes in the liver were studied, including leukocytes, ESR, ALT, AST, GGTP and CRP. The patients’ psycho-emotional status was assessed using a Daily Fatigue Impact Scale (D-FIS) and a four-dimensional scale for assessing distress, depression, anxiety and somatisation (4DSQ). Results. According to the D-FIS questionnaire, all the patients showed fatigue. According to the 4DSQ questionnaire, a correlation of distress with the level of laboratory indicators was revealed among all the patients. No such a correlation was noted for depression and anxiety in the patients with NAFLD. On the contrary, in the case of ALD, all psycho-emotional disorders (except for somatisation) were positively correlated with the markers of inflammation. It is shown that asthenic syndrome in patients with both NAFLD and ALD has a complex origin, being associated both with inflammatory processes in the liver and psycho-emotional disorders. In all cases under study, the prescription of the preparation led to a decrease in the studied laboratory indicators (inflammation markers) and an increase in the patients’ psycho-emotional status. The latter improvement was manifested in the reduction of distress, depression, anxiety and somatisation, according to the 4DSQ questionnaire, as well as in the reduction of fatigue, according to the D-FIS questionnaire.Conclusion. The results of the observational program have shown that patients with NAFLD and ALD frequently experience such components of asthenic syndrome as distress, depression, anxiety, somatisation and fatigue. The prescription of the preparation is found to result in a decrease in laboratory inflammatory indicators. In addition, the preparation is determined to positively affect the components of asthenic syndrome in patients with NAFLD and ALD. In the course of the treatment, no clinically significant side effects were documented.